SPECIFIC ABSORPTION RATE (SAR) DUE TO VARIATION IN FREQUENCY ON HUMAN BODY TISSUES NEAR RADIO BROADCASTING ANTENNA - Kumar, Arvind; Kumar, Vijay; PP, PATHAK (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: Theoretical studies are made for the specific absorption rate (SAR) in consequences of induced electric fields due to radio broadcasting tower at 100 m distance. Methods: The penetrated electric fields and SAR inside human body tissues are calculated for different frequencies. A comparison is made with the international safety guidelines given by World Health Organization and International Commission on Non-ionizing Radiation Protection. Results: The penetrated electric field and SAR by some tissues at frequencies 1377, 1404, 1485, 1512, and 1530 kHz of electromagnetic waves are computed. Conclusion: According to permissible limit the frequencies 1377, 1404, 1485, 1512 and 1530 kHz of 20 kW EM radiations at 100 m distance are safe for tissues bladder, blood vessel, brain white matter, fat, heart, lung outer and mucous membrane at depths 0.1, 0.2 and 0.3 mm respectively. And this radiation is harmful for blood, body fluid, cerebella spinal fluid, eye sclera, gall bladder, gall bladder bile, gland, lung inner, lymph, mucous membrane, pancreas, stomach, testis and vitreous humor tissues at depths 0.1, 0.2 and 0.3 mm, respectively. Keywords: Induced electric field, Specific absorption rate, Thermoregulatory mechanism and broadcasting antenna. Â 